Studi Analisis Optimalisasi Submerged Scraper Chain Conveyor (SSCC) Terhadap Kehandalan Kinerja Boiler PLTU Unit 50 (Universitas Darul Ulum, 2021)
SSCC (Submerged Scraper Chain Conveyor) is one of the parts that affect the combustion process in the Unit 50 PLTU Paiton boiler which can generate electricity up to around 650 MW. SSCC is used to accommodate combustion materials in the form of deposits from inside the boiler. SSCC is also used as a seal for the furnace and prevents air from entering during draft system in service, by keeping the water level in the SSCC at a certain set point value. Even the SSCC stops operating at full load, the unit will potentially debating. This aims to reduce fuel consumption so that the material from the combustion is not too much. The increase in the volume of bottom ash material can cause several problems such as SSCC trips due to overload and loose chain from the pulley. The local operator checks the condition of the bottom ash material on the SSCC scraper at a certain time manually and reports it to the CCR operator. This will affect the reliability of the SSCC's performance on the boiler. This research approach is qualitative, because this research is descriptive and tends to use data analysis. The theoretical basis is used as a guide so that the author can focus on analyzing the data according to the facts in the field. From the results of data analysis applied in the field, it shows that the use of a protection system is the first step in dealing with an incident in the field and to secure other equipment. Based on the work system implemented in the field, namely the SSCC system which was previously operated manually, then changed to auto / easier to operate, it proves that it will create an effective and efficient work system during the unit's operation, thus facilitating the work of operators in the field, as well as improving the quality of equipment which is local. In addition, the development of proposals / ideas that can build a better work system is very much needed in the PLTU generating unit